A Systematic Review of Reading Strategies for EFL Learners with Low Proficiency in Indonesian Senior High Schools - Astuti, Umi; Safitri, Nyimas Triyana; Norawati, Rosinta (Journal of Educational Sciences, 2026)
This paper presents a systematic literature review examining the effectiveness of various reading strategies tailored for English as a Foreign Language (EFL) students with limited proficiency in Indonesian senior high schools. Despite reading being a foundational skill in EFL contexts, numerous national assessments continue to reveal widespread difficulties in reading comprehension among these learners. The review aims to identify practical, research-supported approaches that enhance reading engagement and achievement. Utilizing the PRISMA framework, a total of peer-reviewed articles published from 2014 to 2024 were analyzed, sourced from Scopus, ERIC, and Google Scholar. The quality of each article was assessed using a simplified CASP (Critical Appraisal Skills Programme) framework to ensure methodological rigor and relevance. The review identifies five primary strategies: repeated reading, reciprocal teaching, partner reading, the use of graphic organizers, and digital-based reading tools. These approaches were found to contribute significantly to learner comprehension, motivation, and confidence, particularly in low-proficiency EFL classroom settings.